Transthyretin Promotes Axon Growth via Regulation of Microtubule Dynamics and Tubulin Acetylation - Eira, Jessica; Magalhães, Joana; Macedo, Nídia; Pero, Maria Elena; Misgeld, Thomas; Sousa, Mónica M.; Bartolini, Francesca; Liz, Márcia A. (Frontiers in Cell and Developmental Biology, 2021)
Transthyretin (TTR), a plasma and cerebrospinal fluid protein, increases axon growth and organelle transport in sensory neurons. While neurons extend their axons, the microtubule (MT) cytoskeleton is crucial for the segregation of functional compartments and axonal outgrowth. Herein, we investigated whether TTR promotes axon elongation by modulating MT dynamics. We found that TTR KO mice have an intrinsic increase in dynamic MTs and reduced levels of acetylated α-tubulin in peripheral axons and fail to modulate MT dynamics in response to sciatic nerve injury, leading to decreased regenerative capacity. Importantly, restoring acetylated α-tubulin levels of TTR KO DRG neurons using an HDAC6 inhibitor is sufficient to completely revert defective MT dynamics and neurite outgrowth. In summary, our results reveal a new role for TTR in the modulation of MT dynamics by regulating α-tubulin acetylation via modulation of the acetylase ATAT1, and suggest that this activity underlies TTR neuritogenic function.